Measuring The Performance of Teachers of SMPN 6 Cilegon Based on Self-Concept and Teaching Motivation - Abdul Karim (Yayasan Ilomata, 2021)
Increased teacher performance is influenced by many factors, one of which is self-concept and teaching motivation. This study aims to explain the results of a field study on teacher performance measurement based on self-concept and teaching motivation. This research is a correlational quantitative research. The research subjects were 36 teachers of SMPN 6 Cilegon. Collecting data using a Likert scale questionnaire technique. Research hypothesis testing with product moment correlation analysis and multiple regression analysis. The results showed that self-concept and teaching motivation affected teacher performance by. And among the variables that have the most influence on teacher performance is work motivation as much as self-concept. Based on the research results, the teacher should improve self-concept and teaching motivation. With the increase in these two things, it is hoped that teacher performance can increase.